Sex-Related Differences in Patients With Unexplained Syncope and Bundle Branch Block: Lower Risk of AV Block and Lesser Need for Cardiac Pacing in Women - Francisco-Pascual, Jaume; Rivas-Gándara, Nuria; Bach-Oller, Montserrat; Badia-Molins, Clara; Maymi-Ballesteros, Manel; Benito, Begoña; Pérez-Rodon, Jordi; Santos-Ortega, Alba; Sambola-Ayala, Antonia; Roca-Luque, Ivo; Cantalapiedra-Romero, Javier; Rodríguez-Silva, Jesús; et al. (Frontiers in Cardiovascular Medicine, 2022)
OBJECTIVE: To analyze if there are sex-related differences in patients with unexplained syncope and BBB. BACKGROUND: Despite increasing awareness that sex is a major determinant of the incidence, etiology, and the outcomes of different arrhythmias, no studies have examined differences in presentation and outcomes between men and women with syncope and bundle branch block (BBB) METHODS: Cohort study of consecutive patients with unexplained syncope and BBB included from January 2010 to January 2021 with a median follow-up time of 3.4 years [IQR 1.7-6.0 years]. They were evaluated by a stepwise work-up protocol based on electrophysiological study (EPS) and long-term follow-up with an implantable cardiac monitor (ICM). RESULTS: Of the 443 patients included in the study, 165 (37.2%) were women. Compared with men, women had less diabetes (25.5% vs. 39.9%, p 0.002) and less history of ischemic heart disease (13.3% vs. 25.9%, p 0.002). LBBB was more frequent in women (55.2% vs. 27.7%, p <0.001) while RBBB was more frequent in men (41.5% vs. 67.7%, p <0.001). HV interval in the EPS was shorter in women (58 msec [IQR 52-71] vs 60 msec [IQR 52-73], p=0.035) and less women had an HV interval longer than 70 msec. (25.5% vs. 38.1%, p=0.039), however EPS and ICM offer a similar diagnostic yield in both sexes (40.6% vs. 48.9% and 48.4% vs. 51.1% respectively). Women had a lower risk of developing atrioventricular block (AVB) (adjusted OR 0.44 – 95% CI 0.26-0.74, p 0.002) and of requiring permanent pacemaker implantation (adjusted HR 0.72 - 95% CI: 0.52-0.99, p=0.046). The mortality rate was lower in women (4.5 per 100 person-years [95% CI 3.1-6.4 per 100 person-years] vs. 7.3 per 100 person-years [95% CI 5.9-9.1 per 100 person-years]. CONCLUSIONS: Compared to men, women with unexplained syncope and BBB have a lower risk of AVB and of requiring cardiac pacing. A stepwise diagnostic approach has a similar diagnostic yield in both sexes, and it seems appropriate to guide the treatment and avoid unnecessary pacemaker implantation, especially in women.